312 Lysine Requirement of Lactating Sows - Revisited. (10th April 2018) - Graham, A; Greiner, L; Goncalves, M A D; Orlando, U A D; Touchette, K J
Abstract: An experiment was conducted with 351 sows (PIC Camborough) to evaluate the effects of SID lysine intake on sow and litter performance during a 23-d lactation period. Sows were randomly allotted within parity block (parity 1, parity 2, and parity 3+) to one of five corn soybean meal based lactation diets formulated to contain different levels of SID lysine (49, 57, 65, 73, and 81 g/d, respectively). All diets were formulated to be isocaloric (3.3 ME Mcal/kg) and contained vitamins and minerals that exceeded recommendations (NRC, 2012). Experimental diets were given to sows from 112 d of pregnancy throughout the 23-d lactation period. Litters were standardized within 48 h after farrowing, and sows were allowed 5.9 kg of feed/d throughout the lactation period. Sows were fed with a computerized feeding system to record daily sow feed intake during lactation. Data were analyzed as a randomized complete block design using the PROC MIXED procedure of SAS with sow as the experimental unit and treatment as a fixed effect and parity as the random effect. Results were considered significant at P ≤ 0.05 and considered a trend at P > 0.05 and P ≤ 0.10. There were approximately 70 replications per treatment. Sow ADFI was lower ( P >0.10) than calculated (5.14, 5.05, 5.20, 5.19, 5.15 kg/d) resulting in a SID Lys daily intake of 42.8, 48.9, 57.4, 64.5, 71.1, respectively. Increasing dietary lysine intake resulted in a significant linear increase (2.04, 2.42, 2.80, 3.16, 3.47; P < 0.05) in litter average daily gain as dietary lysine increased. There were no differences in wean to estrus interval, sow weight loss, or subsequent total born across the dietary treatments. Overall, increasing levels of SID lysine resulted in a linear increase in litter average daily gain during lactation with no major influence in the other parameters. The lower than expected lactation intake could have caused energy to be a limiting factor in this study.